2017
DOI: 10.1111/jth.13684
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of platelet P2Y12 receptors to chronic Complete Freund's adjuvant‐induced inflammatory pain

Abstract: Background P2Y receptor antagonists are widely used in clinical practice to inhibit platelet aggregation. P2Y receptors are also known to regulate different forms of pain as well as local and systemic inflammation. However, it is not known whether platelet P2Y receptors contribute to these effects. Objectives To explore the contribution of platelet P2Y receptors to chronic inflammatory pain in mice. Methods Complete Freund's adjuvant (CFA)-induced chronic inflammatory pain was induced in wild-type and P2ry12 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 51 publications
(94 reference statements)
2
31
0
1
Order By: Relevance
“…However, previous studies have not yet fully clari ed it mechanisms of action. Cangrelor is a second-generation P2Y12, and past studies have found that cangrelor alleviates the in ammatory response in lung brosis [21], chronic in ammatory pain [22], and neuropathic pain [23]. In the present study, we found that cangrelor decreased CLP-induced pulmonary injury by modulating the in ammatory response.…”
Section: Discussionsupporting
confidence: 67%
“…However, previous studies have not yet fully clari ed it mechanisms of action. Cangrelor is a second-generation P2Y12, and past studies have found that cangrelor alleviates the in ammatory response in lung brosis [21], chronic in ammatory pain [22], and neuropathic pain [23]. In the present study, we found that cangrelor decreased CLP-induced pulmonary injury by modulating the in ammatory response.…”
Section: Discussionsupporting
confidence: 67%
“…5D). To verify that PSB injected intra-cisterna magna only inhibited microglial P2Y12 receptors, and not those expressed by circulating platelets, we measured ADP-induced platelet activation in plasma samples 1 hour after MCAo, when blood-brain barrier injury is apparent (37,39,40). ADP-induced increases in platelet CD62P were not altered in mice treated with intra-cisterna magna PSB compared with vehicle-treated animals ( fig.…”
Section: Microglia Protect Neurons After Acute Brain Injury In a P2y1mentioning
confidence: 99%
“…Of interest due to the clinical availability of several selective antagonists (see below), a recent paper demonstrated that P2Y12 receptors expressed by platelets contribute to hyperalgesia and local inflammation in a chronic Complete Freund's Adjuvant (CFA)-induced inflammatory pain model in mice (Bekő et al, 2017). Authors demonstrated that P2Y12-/-mice developed milder signs of CFAinduced pain with respect to wild-type animals, in parallel with reduced signs of inflammation of the hind paw.…”
Section: Adenosine and P2y Receptors In Inflammatory Pain And In Migrmentioning
confidence: 99%
“…Although the concomitant activity on platelets could pose some safety problems, the evaluation of these drugs in different types of pain syndrome could therefore be accelerated by the availability of pharmacokinetics and pharmacodynamics data despite that the appropriate route of administration is identified to reach the CNS target on microglia cells. Interestingly in view of preclinical data showing a possible role for platelet P2Y12 receptors in the modulation of pain (see above; Bekő et al, 2017), genetic variability in the P2Y12 gene seems to contribute to individual differences in pain and opioid sensitivity. A recent study genotyped 31 single nucleotide polymorphisms (SNPs) throughout the P2Y12 gene and compared the different genotypes with pain severity in 90 cancer patients, and with a cohort of patients suffering from post-operative pain.…”
Section: When Will a Purinergic-based Drug Reach The Market As Innovamentioning
confidence: 99%